2002
DOI: 10.22237/jmasm/1036110540
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Nonparametric Statistics And Their Large Sample Approximations

Abstract: Nonparametric procedures are often more powerful than classical tests for real world data which are rarely normally distributed. However, there are difficulties in using these tests. Computational formulas are scattered throughout the literature, and there is a lack of availability of tables and critical values. The computational formulas for twenty commonly employed nonparametric tests that have large-sample approximations for the critical value are brought together. Because there is no generally agreed upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Secondly, both of the tested samples had to come from the same type of distribution function differing only in scale. To test this assumption, another rank type test was used, namely Wilcoxon rank sum test [Fahoome 2002]. This let the author check whether H 0 stating that two independent samples used in particular Ansari--Bradley's procedure were selected from the same distributions without statistically significant differences in location parameters.…”
Section: Data and Research Methodsmentioning
confidence: 99%
“…Secondly, both of the tested samples had to come from the same type of distribution function differing only in scale. To test this assumption, another rank type test was used, namely Wilcoxon rank sum test [Fahoome 2002]. This let the author check whether H 0 stating that two independent samples used in particular Ansari--Bradley's procedure were selected from the same distributions without statistically significant differences in location parameters.…”
Section: Data and Research Methodsmentioning
confidence: 99%
“…The large-sample approximation to the sampling distribution of Page's L statistic yields acceptable Type I error rates for a directional Page test, as long as n > 11 for α = .05, or n > 18 for α = .01, according to Fahoome (2002). An acceptable Type I error rate was defined in Fahoome (2002) as within 10% of the nominal α rate, in reference to Bradley (1978)'s work.…”
Section: Six Page Tests Of Trendsmentioning
confidence: 99%
“…An acceptable Type I error rate was defined in Fahoome (2002) as within 10% of the nominal α rate, in reference to Bradley (1978)'s work. Page (1963) also suggested that the large-sample chi-square approximation be used under one of three conditions: (1) for m > 20 with any n, (2) for m > 12 and n ≥ 4, or (3) for any m when n ≥ 9.…”
Section: Six Page Tests Of Trendsmentioning
confidence: 99%
See 2 more Smart Citations